Transparency: the main foundation to combat corruption in public procurement (2016)
In this paper we contextualize and exposed to general feature, The General Contracting Public Administration, Law 80 of 1993. Then, it will outline the guiding principle of government contracting, entitled Transparency Principle, this enshrined in the Statute. Then, the grounds for its creation, the political and legal environment and what are the purposes of this, so, check whether they are indeed complying with the thought and specifically, if this basis of public procurement has been or will not be discussed it has been fighting its main purpose, which is to reduce the levels of corruption and impartiality in State offices.